Implementing a sustainable integrated agroforestry system for the cultivation of Ilex paraguariensis - Comolli, Luis R.; Schegg, Esteban; Infuleski, Cristian; Munareto, Nestor; Fassola, Hugo; von Wallis, Alejandra; Bulfe, Nardia M.; González, Paola; Barth, Sara R.; Gauchat, María Elena; Wyss, Fabio (Frontiers in Forests and Global Change, 2024)
In this work, we advocate agroforestry as a sustainable agricultural method that leverages biodiversity and ecosystem services, simultaneously tackling the problems of adaptation and mitigation to climate change, and of land restoration for sustainable agriculture across scales. While the rise of industrial agriculture has been instrumental in addressing the food demands of an expanding global population, enhancing food quality, yield, productivity, and efficiency, we must now reckon with the consequences. This advancement, which prioritizes simplification, specialization, and external inputs, has escalated detrimental externalities including deforestation, biodiversity loss, soil degradation, pollution, and an increase in greenhouse gases, contributing significantly to global warming and to exacerbated environmental crises. These demand urgent attention. In response, various agricultural methodologies such as organic, biodynamic, ecological, and biological farming have emerged, attempting to propose alternatives. However, these methods have yet to significantly alter the trajectory of mainstream agriculture. For over two decades, we have devoted our efforts to developing and refining a multispecies integrated agroforestry system for the sustainable cultivation of Ilex paraguariensis, “yerba mate,” in the subtropical north-east of Argentina. With “integrated” we mean that the trees are planted within the I. paraguariensis distribution, not between alleys as in “alley cropping” or “hedgrow intercropping.” The experimental work we present here was designed and implemented to enable data comparisons across consociations of multiple species of trees, at a relevant experimental scale. We achieve soil preservation and restoration, productivity comparable to or exceeding monocultures, and a significant increase in resiliency, particularly evidenced during the extreme climate events of spring and summer 2021 and 2022. These results underscore agroforestry’s potential for climate change mitigation and adaptation.